Improving Student Learning Outcomes in Learning Descriptive Texts by Applying the Culturally Responsive Teaching (CRT) Approach Through Flashcard Media in Grade VII SMPN 51 Surabaya - Agnestina, Dewi Sandriya; Dwi Ernawati; Titik Indarti (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to improve the learning outcomes of Indonesian descriptive text material in the hope of increasing the learning completeness of students. This research is a collaborative classroom action research carried out in two cycles, with the stages of planning, acting, observing, and reflecting activities, which are repeated until the second cycle and end with a conclusion. Based on the results of the study, there was a significant increase in learning outcomes. The results showed that in cycle 1 the percentage of student completeness was 63%, while in cycle 2 the percentage of completeness increased to 89%. Thus, it can be concluded that the application of the Culturally Responsive Teaching (CRT) learning approach through Flashcard learning media can improve the learning outcomes of students in grade VII D at SMP Negeri 51 Surabaya. Keywords : Culturally Responsive Teaching (CRT) approach, Flashcard learning media, descriptive text, classroom action research (PTK), learning outcomes